Risk communication and the prevention of COVID-19 transmission among community of educators in dangerous zones - Imam Nuraryo, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Until the beginning of June 2020, the COVID-19 virus has spread to more than 215 countries, infected more than 6 million people and killed more than 300,000 people in the world. This causes public panic and misperceptions about COVID-19. Under circumstances like this, risk communication is needed to control and mitigate information about this plague to reduce the spread of this disease and manage public fear. The main objective of this study is to assess COVID-19 information searching behaviour and explore how risk communication is associated with personal hygiene habits in preventing transmission of COVID-19 in dangerous zones. This study was conducted among a community of educators in Jakarta, Bogor, and Tangerang, Indonesia. Questionnaires were distributed to 132 respondents, consisting of lecturers and teachers who are living in the red zone area. The results showed that there was no relationship between the perception of risk communication, both on personal hygiene habits and prevention of COVID-19 transmission. This can be attributed to two possibilities. Firstly, the risk communication message strategy is seen as irrelevant to people’s personal hygiene habits and prevention of COVID-19 transmission. Secondly, personal hygiene habits and prevention of COVID-19 transmission are not influenced by risk communication from the government and at media level.